Evaluation of local and regional spread of malignant tumors of the tongue and floor of the mouth - Dimitrijević Milovan; Đukić Vojko; Trivić Aleksandar (Vojnosanitetski Pregled)
Malignant tumors of the oral cavity grow rapidly, frequently and early metastazing to the surrounding regional lymph nodes. The aim of this study was to evaluate the correlation between clinically confirmed local and regional spread and intraoperatively and histopathologically verified local spread. A series of 74 patients with carcinoma of the tongue and floor of the mouth were analyzed. All the patients were surgically treated during the period 1991-1995. Clinical evidence of local spread (cT) was in high accord with intraoperatively and histopathologically evidenced spread (pT) amounting to 83.8%. The degree of correlation decreased with the increase of T stage. Clinically observed regional spread (cN) and intraoperatively and histopathologically confirmed regional spread (pN) was lower, amounting to 56.8% in comparison to the corresponding T categories.